Report of the Group of Secretaries on Policy Outline for Reduction in Imports of Capital Goods for Public Sector Projects Volume-II - Planning Commission (Planning Commission, 1985)
Coal sector is one of the largest capital goods consumers. As distinct from sectors such as Power, and Steel, the demand from this sector is not widely fluctuating. It is characterised by a relatively large number of projects of varying capacities. Though the capital goods required are not custom built, yet the quantities of each type of equipment are such as are not amendable to a sizeable batch of production.
Government of India, Planning Commission